2020
DOI: 10.5089/9781513526034.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Output Effect of Fiscal Policy Shocks in Low Income Countries

Abstract: What do we know about the output effects of fiscal policy in low income countries (LICs)? There are very few empirical studies on the subject. This paper fills this gap by estimating the output effects of government spending shocks in LICs. Our analysis—based on the local projection method—finds that the output effects in LICs are markedly lower than those in AEs and marginally smaller than those in EMs. We also find that in LICs, the output effects are larger (i) during recessions; (ii) under a fixed exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 23 publications
5
29
0
Order By: Relevance
“…This is in part due to data limitations and difficulties in identifying fiscal policy shocks.10 Available empirical studies suggest that the impact of fiscal policy on output in developing countries is lower than in advanced economies and perhaps more short-lived.11 Specifically, government consumption cuts have a temporary impact on output, but public investment shocks have a larger and longer-lasting effect, as the private sector is small and public investment is essential for economic growth. In addition, as with advanced economies, the output effects appear to be larger during recessions (Honda et al 2020).…”
Section: Impact Of Economic Crises On Inclusivenessmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in part due to data limitations and difficulties in identifying fiscal policy shocks.10 Available empirical studies suggest that the impact of fiscal policy on output in developing countries is lower than in advanced economies and perhaps more short-lived.11 Specifically, government consumption cuts have a temporary impact on output, but public investment shocks have a larger and longer-lasting effect, as the private sector is small and public investment is essential for economic growth. In addition, as with advanced economies, the output effects appear to be larger during recessions (Honda et al 2020).…”
Section: Impact Of Economic Crises On Inclusivenessmentioning
confidence: 95%
“…On the revenue side, a larger share of revenues comes from indirect taxes, which tend to be regressive. Therefore, tax hikes could be detrimental to welfare, especially for the poor.14 In terms of the timing, similar to cases for advanced economies, fiscal consolidation undertaken during recessions tends to have a larger impact on unemployment and inequality (Honda, Miyamoto, and Taniguchi 2020).…”
Section: Impact Of Economic Crises On Inclusivenessmentioning
confidence: 99%
“…Most of the empirical research on the macroeconomic effects of fiscal policy has focused on the developed countries, mainly the U.S., Europe and Australia. In the context of low-income countries (LICs), the paper by Honda et al (2020) estimates the impulse response of output to fiscal policy shocks using the local projection method and reveals that the output effects are more significant: (a) during a recession; (b) under a fixed exchange rate regime; and/or (c) with better institutional quality. Using annual data for 1995-2017 from the International Monetary Fund's database, the author finds that the state of an economy and its structural characteristics are important for estimating the output effects of fiscal spending shocks.…”
Section: Literature Surveymentioning
confidence: 99%
“…Szymanska (2018) using a three-variable SVAR model, in accordance with the approach of Blanchard and Perotti (1999), investigated the effects of expenditure shocks for three EEC countries (Czech Republic, Hungary and Poland), the results obtained indicating a positive response in regards to their production. Honda et al (2020) identified a differentiation of the effects of government spending shocks according to the degree of the countries' development. Baranowski et al (2016) showed that the government spending multipliers are significantly higher when the output gap is negative.…”
Section: The Impulse -Response Functionmentioning
confidence: 99%